دور CHAT GPT المدعم بالذكاء الاصطناعي في تقديم خدمات مبتكرة - أمحمد بغدادي; عماد الدين جفال (university of eloued جامعة الوادي, 2024)
"الملخص تهدف هذه الدراسة إلى معرفة دور تطبيق ChatGPT المدعوم بالذكاء الاصطناعي في تقديم خدمات مبتكرة وتحسين تجربة المستخدم في عدة مجالات، مع التركيز على التعليم. توضح الدراسة كيف يمكن لهذه التقنية الثورية تحقيق تطورات هائلة بفضل قدرتها على فهم اللغة الطبيعية وتوليد ردود فعالة وذكية. تم الاعتماد على توزيع استبيان واستخدم المنهج الوصفي لتحليل الظاهرة أما في الجانب التطبيقي، اعتمدنا على المنهج التحليلي لاختبار وتحليل استبيانات موزعة على 60 طالبًا وأستاذا من كلية العلوم الاقتصادية والتجارية وعلوم التسيير بجامعة الوادي. أظهرت النتائج أن ChatGPT يحسن جودة الخدمات التعليمية ويزيد من التفاعل والمشاركة الإيجابية، وأوصت الدراسة بدمج تقنيات الذكاء الاصطناعي في المناهج التعليمية وتوفير تدريب لأعضاء هيئة التدريس." "Summary: This study aims to explore the role of ChatGPT, powered by artificial intelligence, in delivering innovative services and enhancing user experience across various fields, with a focus on education. The study demonstrates how this revolutionary technology can achieve significant advancements through its ability to understand natural language and generate effective, intelligent responses. A literature review of books, articles, and publications was conducted, utilizing a descriptive approach to describe the phenomenon. For the practical part, an analytical method was used to test and analyze questionnaires distributed to 60 students and professors from the Faculty of Economic, Commercial, and Management Sciences at the University of El Oued. Results indicated that GPT Chat improves the quality of educational services and increases positive interaction and participation. The study recommends integrating AI technologies into curricula and providing training for faculty members."
Keywords: Chat GPT، الذكاء الاصطناعي، خدمات مبتكرة، تقديم خدمات، التعلم; ChatGPT; artificial intelligence; innovative services; service delivery; learning